Family Mediation: A Guide for Family Therapists. Issue 4 (December 2014) - Morris, Megan; Halford, W. Kim
<x xml:space="preserve">Abstract</x> Family therapists often see separating parents who need to agree on co‐parenting arrangements. This article provides a guide to current research and practice in family mediation. The limited available research suggests mediation is a useful approach for some separated parents and their children, but often is not successful with highly conflicted parents, parents with mental health problems, parents struggling to accept the separation from their partner, or parents with unrealistic co‐parenting expectations. We analyse ways in which mediation might be enhanced, and discuss the potential roles of family therapists to support separating families to negotiate positive co‐parenting.